Glycopeptide-nanotransforrs eyedrops with enhanced permeability and retention for preventing fundus neovascularization. (February 2022) - Li, Ke; Li, Ruxiang; Zou, Pengfei; Li, Li; Wang, Huajun; Kong, Deqian; Zheng, Guangying; Li, Li-Li
Abstract: Efficient and non-invasive drug delivery to the fundus has always been a medical difficulty. Here, a co-assembled glycopeptide nanotransforrs (GPNTs) named MRP@DOX as a drug delivery system is reported. The MRP@DOX co-assemble nanoparticles consisting of glycopeptide, cationic peptide, and doxorubicin (DOX). The nanoparticles are positively charged with the nano-size, which can be induced transformation by legumain cleavage. Once administrate to the eyes, MRP@DOX has a high penetration through the ocular surface to specifically targets M2 macrophages in the fundus. Then, the mannose receptor mediates phagocytosis and intracellular highly expressed legumain induces its nanofibrous transformation, which contributes to a 44.7% DOX retention in cells at 24 h than that of the non-transformed controls (MAP@DOX : 5.1%). The nanofiber transformation provides an inhibition of exocytosis, which explains the higher retention of the delivered drug. In the mouse OIR model, MRP@DOX completely restores the physiological angiogenesis and reduces pathological neovascularization. Pathological neovascularization branches and cell nuclei that break through the inner limiting membrane are reduced by 55% and 72%, respectively, which are 25% and 20% less than those in the non-transformed controls. In addition, MRP@DOX also has good histocompatibility, which provides a possible strategy for non-invasive treatment of fundus diseases in the future.